Treasure lying beneath the waters: exploring the deep connections between biodiversity and the blue economy - Çamkaya, Serhat; Kaya, Emine; Barut, Abdulkadir; Ali, Kishwar; Pilatin, Abdulmuttalip; Nassani, Abdelmohsen A. (Frontiers in Marine Science, 2025)
IntroductionThe blue economy has become a pivotal framework for achieving sustainable development, emphasizing the responsible utilization of marine and coastal resources while preserving ecosystem integrity. Although biodiversity is central to fisheries, aquaculture, and coastal tourism, its direct role in shaping the blue economy remains underexplored. Furthermore, the interactions of biodiversity with other structural factors, such as financial development, institutional quality, and environmental pressures, are insufficiently addressed in existing studies.MethodsThis study investigates the determinants of the blue economy by employing panel data from the world’s ten highest-income blue economies over the period 2000–2021. To address econometric challenges such as cross-sectional dependence, unit roots, and cointegration, second-generation panel techniques were applied. Long-term relationships were estimated using the Augmented Mean Group (AMG) estimator, and robustness was assessed through complementary econometric tests.ResultsThe empirical findings demonstrate that biodiversity exerts a positive and statistically significant effect on the blue economy. In contrast, financial development is negatively associated with blue economy performance. Institutional quality and per capita income are found to enhance blue economy outcomes, while CO₂ emissions exert a detrimental influence. Robustness checks confirm the stability and reliability of these results across alternative specifications.DiscussionThe results underscore the vital role of biodiversity conservation in fostering sustainable growth within the blue economy framework. However, the negative effect of financial development suggests that existing financial structures do not sufficiently channel resources into environmentally sustainable marine activities. Strengthening institutional frameworks and aligning financial systems with ecological priorities are therefore critical. Moreover, reducing carbon emissions is indispensable to securing long-term resilience of marine ecosystems and ensuring the sustainability of blue economy activities.